Imitation as a mechanism in cognitive development: a cross-cultural investigation of 4-year-old children’s rule learning - Wang, Zhidan; Williamson, Rebecca A.; Meltzoff, Andrew N. (Frontiers in Psychology, 2015)
Children learn about the social and physical world by observing other people’s acts. This experiment tests both Chinese and American children’s learning of a rule. For theoretical reasons we chose the rule of categorizing objects by the weight. Children, age 4 years, saw an adult heft four visually-identical objects and sort them into two bins based on an invisible property—the object’s weight. Children who saw this categorization behavior were more likely to sort those objects by weight than were children who saw control actions using the same objects and the same bins. Crucially, children also generalized to a novel set of objects with no further demonstration, suggesting rule learning. We also report that high-fidelity imitation of the adult’s “hefting” acts may give children crucial experience with the objects’ weights, which could then be used to infer the more abstract rule. The connection of perception, action, and cognition was found in children from both cultures, which leads to broad implications for how the imitation of adults’ acts functions as a lever in cognitive development.